Karakteristik dan Profil Inulin Beberapa Jenis Uwi (Dioscorea spp.) - Sri Winarti; Eni Harmayani; Rudi Nurismanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
Wild yams (Dioscorea spp.) grow well in Indonesia known as Uwi, is the kind of tubers that grow in the community,but they have not been used optimally. Publicity about the characteristics and types has been limited. The tubers contain inulin, but also there have been no publication related.The purpose of this study was to uncover the characteristics of wild yam and inulin profiles contained in the tubers.The yams were obtained from various regions in East Java, among others Pacet Mojokerto, Karang Ploso and Kawi Mountains in Malang, Nganjuk, and traditional markets in Surabaya.The tubers were characterized for shape and size of tubers, skin color and flesh tubers, average weight and texture of the tuber, moisture content, ash content and levels of inulin, texture and flavor. The data were analyzed using Analysis of Variance (ANOVA) and further test Duncan’t Multiple Range Test (DMRT).Based on the characteristics of tubers, there were 10 types of wild yams, namely D1 (Dioscororea alata/ white yam), D2 (Dioscorea pinthaphylla/frog yam), D3 (Dioscorea hispida /Gadung), D4 (Dioscorea alata /purple yam with yellow skin), D5 (Dioscorea alata /purple yam), D6 (Dioscorea esculenta/gembili), D7 (Dioscorea alata/yellow yam), D8 (Dioscorea opposita/white yam with yellow skin), D9 (Dioscorea bulbifera/gembolo) and D10 (Dioscorea rotundata/ white yam with brown skin). The highest levels of inulin obtained in Dioscororea esculenta (gembili) ie 14.77 % (db). The water content rangedbetween 71.89- 85.07 % (wb), ash content 0.59- 1.83 % and texture between 0.012 to 0.055 (mm/g.dt). Organoleptic score was 2.75 to 4.55 texture and taste is from 3.20 to 5.00.ABSTRAKUwi merupakan jenis umbi-umbian yang tumbuh di Indonesia, namun belum dimanfaatkan secara optimal dan belumbanyak publikasi mengenai kharakteristik dan jenis-jenisnya. Uwi mengandung inulin, namun belum banyak publikasi yang mengungkap kadar inulin pada berbagai jenis umbi uwi tersebut.Tujuan dari penelitian ini adalah mengetahui kharakteristik fisik dan kimia jenis-jenis umbi uwi (Dioscorea spp.), serta profil inulin yang terkandung dalam masing-masing umbi.Beberapa jenis uwi diperoleh dari berbagai daerah di Jawa Timur, antara lain Pacet Mojokerto, Karang Ploso dan Pegunungan Kawi Malang, Nganjuk, dan pasar tradisional Surabaya. Karakteristik fisik yang diamati meliputi , bentuk dan ukuran umbi, warna kulit dan daging umbi, berat rata-rata dan tekstur umbi. Karakteristik kimia yang diamati meliputi kadar air, kadar abu dan kadar inulin. Karakteristik organoleptik pada uwi kukus yang diamati adalah tekstur dan rasa. Data yang diperoleh dianalisis menggunakan Analisis Varian (ANOVA) dan uji lanjut Duncan’t Multiple Range Test (DMRT).Dari hasil karakterisasi diperoleh 10 jenis uwi yaitu D1 (Dioscororea alata/uwi putih), D2 (Dioscorea pinthaphylla/ uwi katak), D3 (Dioscorea hispida/uwi gadung), D4 (Dioscorea alata/uwi kuning kulit ungu), D5 (Dioscorea alata/ uwi ungu), D6 (Dioscorea esculenta/gembili), D7 (Dioscorea alata/uwi kuning), D8 (Dioscorea opposita/uwi putih kulit kuning), D9 (Dioscorea bulbifera/gembolo), dan D10 (Dioscororea rotundata/uwi putih kulit coklat).Kadar inulin tertinggi diperoleh pada Dioscororea esculenta (gembili) yaitu 14,77 % (db). Kadar air berkisar antara71,89-85,07 % (wb), kadar abu 0,59-1,83 % dan tekstur antara 0,012-0,055 (mm/g.dt). Skor organoleptik tekstur adalah 2,75-4,55 dan rasa adalah 3,20-5,00.